Perhitungan Harga Pokok Produksi Melalui Metode Full Costing dalam Industri Tahu Putra Gunung Jimat - Regita Eriska Dewi; Nazwa Aulia Triyani; Fanny Nur Qhotimah; Yuni Astuti Tri Tartiani (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This study aims to calculate the cost of production (COP) using the full costing method at Tahu Putra Gunung Jimat Factory located in Depok. This factory produces tofu with soybeans as the main raw material and faces challenges in accurately calculating the COP to set the right selling price and maintain profitability. The full costing method is used to include all production costs, both fixed and variable, which consist of raw material costs, direct labor costs, and factory overhead costs. The results show that the total monthly production cost amounts to Rp 330,861,458, with the cost of production per tofu unit calculated at Rp 812.15. The full costing method enables the factory to have a comprehensive view of the expenses incurred in the production process, allowing it to determine more accurate selling prices and adopt more effective market strategies. These findings align with previous studies, highlighting the importance of this method for Small and Medium Enterprises (SMEs) to sustain competitiveness and business continuity. The study also suggests that future research should consider the impact of production volume on fluctuations in the cost of production.